Novel beaded polymers from telechelic methacrylic ether esters - Pujari, N. S.; Trivedi, J.; Ingavle, Ganesh C.; Ponrathnam, S. (Reactive & Functional Polymers, 2006)
A series of telechelic dimethacrylic ether-esters (MEE) were prepared by solventless reaction of alpha,omega-dihydroxy poly(oxytetramethylene) (polytetrahydrofuran, PTHF) with phthalic anhydride and glycidyl methacrylate (GMA). MEE was polymerized with GMA as well as GMA-ethylene dimethacrylate (EGDM) to form porous beads. The terpolymer beads were observed using optical microscopy and SEM and characterized for internal pore volume, equilibrium volume-swelling ratio and dimethyl formamide and aqueous buffer regain. The morphology of the beads was dictated by the mole fraction and molecular weight of MEE in the feed. Porosity was found to increase with increase in molecular weight of MEE. Thus, porosity as high as 49%, 50% and 55% was observed with MEE of molecular weights 1580, 2580 and 3480, respectively. At a specific terpolymerization feed ratio of monomers, the terpolymers formed transform from gel like structure into a macroporous one, with increase in molecular weight of MEE. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ether-ester dimethacrylates; macroporous; Pore size distribution; porosity; telechelics